MULTIPLIKASI IN VITRO ANGGREK HITAM (Coelogyne pandurata Lindl.) PADA PERLAKUAN KOMBINASI NAA DAN BAP - Kartiman, Roni; Sukma, Dewi; Aisyah, Syarifah Iis; Purwito, Agus (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2018)
In Vitro Multiplication of  Black Orchid (Coelogyne pandurata Lindl.) Using the Combination of NAA and BAPABSTRACTBlack orchid is an indigenous plant from Kalimantan, Indonesia. It becomes endangered because of forest over-exploitation and its low natural reproduction rate. Tissue culture is considered to offer a solution to conserve and propagate this species. The aim of this research was to evaluate the effect of Naphtalene Acetic Acid (NAA) and 6-Benzile Amino Purine (BAP) on shoots multiplication of black orchid. The basic medium used was a half of Murashige & Skoog (MS) composition supplemented with 150 mLL-1 coconut water. Initial explants used were 6-month-old shoots of germinating seeds. The shoot cultures were incubated for 23 weeks. Results showed that the best combination for shoot multiplication was NAA 0.0 mgL-1 with BAP 0.2 mgL-1. Shoot grew better on medium with BAP and without NAA while roots growth was better on medium without the two plant growth regulators. The addition of BAP up to 0.3 mgL-1 increased the leaf number, which however decreased at higher BAP concentration.Keywords: BAP, black orchid, Coelogyne pandurata, multiplication, NAA ABSTRAKAnggrek hitam merupakan flora langka asli Kalimantan, Indonesia. Keberadaa anggrek ini di alam semakin langka akibat eksploitasi berlebihan dan sulitnya perbanyakan secara alami. Kultur jaringan merupakan metode untuk mengatasi kelangkaan anggrek ini. Penelitian ini bertujuan untuk mengetahui pengaruh kombinasi NAA dan BAP terhadap multiplikasi anggrek hitam. Media dasar yang digunakan adalah ½ MS dengan penambahan air kelapa 150 mLL-1. Eksplan yang digunakan adalah tunas hasil semai biji umur 6 bulan. Kultur tunas diinkubasi selama 23 minggu. Hasil penelitian menunjukkan bahwa kombinasi terbaik untuk multiplikasi tunas adalah NAA 0 mgL-1 dengan BAP 0,2 mgL-1. Tunas tumbuh lebih baik dalam media dengan penambahan BAP tanpa NAA, sedangkan akar pada media tanpa NAA dan BAP. Penambahan BAP sampai 0.3 mgL-1 mampu meningkatkan jumlah daun, namun menurun dengan penambahan di atas konsentrasi tersebut.Kata Kunci: anggrek hitam, BAP, Coelogyne pandurata, multiplikasi, NAA